Highly Stretchable and Transparent Metal Nanowire Heater for Wearable Electronics Applications. (14th July 2015) - Hong, Sukjoon; Lee, Habeom; Lee, Jinhwan; Kwon, Jinhyeong; Han, Seungyong; Suh, Young D.; Cho, Hyunmin; Shin, Jaeho; Yeo, Junyeob; Ko, Seung Hwan
<x xml:space="preserve">Abstract</x> A highly stretchable and transparent electrical heater is demonstrated by constructing a partially embedded silver nanowire percolative network on an elastic substrate. The stretchable network heater is applied on human wrists under real‐time strain, bending, and twisting, and has potential for lightweight, biocompatible, and versatile wearable applications.